2018
DOI: 10.1186/s13045-018-0562-z
|View full text |Cite
|
Sign up to set email alerts
|

CBX7 regulates stem cell-like properties of gastric cancer cells via p16 and AKT-NF-κB-miR-21 pathways

Abstract: BackgroundChromobox protein homolog 7 (CBX7), a member of the polycomb group (PcG) family of proteins, is involved in the regulation of cell proliferation and cancer progression. PcG family members, such as BMI, Mel-18, and EZH2, are integral constituents of the polycomb repressive complexes (PRCs) and have been known to regulate cancer stem cell (CSC) phenotype. However, the role of other PRCs’ constituents such as CBX7 in the regulation of CSC phenotype remains largely elusive. This study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 52 publications
(65 reference statements)
2
89
0
Order By: Relevance
“…In addition, previous studies demonstrated that celastrol inhibited the PI3K/AKT and NF-κB survival pathway in human breast cancer (Shrivastava, Jeengar, Reddy, Reddy, & Naidu, 2015). Moreover, miR-21 can affect cancer cell growth via regulating the PTEN/AKT and NF-κB pathways (He et al, 2015;Ni et al, 2018;S. M. Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, previous studies demonstrated that celastrol inhibited the PI3K/AKT and NF-κB survival pathway in human breast cancer (Shrivastava, Jeengar, Reddy, Reddy, & Naidu, 2015). Moreover, miR-21 can affect cancer cell growth via regulating the PTEN/AKT and NF-κB pathways (He et al, 2015;Ni et al, 2018;S. M. Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, previous studies demonstrated that celastrol inhibited the PI3K/AKT and NF‐κB survival pathway in human breast cancer (Shrivastava, Jeengar, Reddy, Reddy, & Naidu, ). Moreover, miR‐21 can affect cancer cell growth via regulating the PTEN/AKT and NF‐κB pathways (He et al, ; Ni et al, ; S. M. Yang et al, ). Furthermore, PTEN/PI3K/AKT and NF‐κB signaling pathways are often involved in gastric cancer (Baud & Karin, ; Colombo, Zambrano, & Agresti, ; He et al, ; Sha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-21 was involved in the regulation of a number of Polycomb group (PcG) proteins on gastric cancer stem cells (CSCs), a small subset of cancer cells with self-renewal and tumor-initiating properties, which are critical in tumor metastasis, recurrence and chemoresistance (70). PcG family proteins, including polycomb group RING finger protein 2 (Mel-18), chromobox homolog 7 (CBX7) and enhancer of zeste homolog 2, form the multi-protein complexes, called polycomb repressive complexes, through which they epigenetically regulate homeotic genes expression by altering chromosomal structure or transcriptional repression (71). In this manner, PcG proteins exert effects in embryonic development, cell proliferation and differentiation, stem cell properties and tumorigenesis (71).…”
Section: Pten Mediates Oncogenic Activities Of Mirnas Via Pi3k/akt Simentioning
confidence: 99%
“…MiR‐29b promotes cisplatin resistance in GC cells via the PI3K/Akt signaling pathway . Apart from serving roles downstream of the PI3K/Akt pathway, NF‐κB used to be moreover capable to have an effect on the expression of PTEN and downstream Akt signaling, mediated through its transcriptional regulation of miRNAs, consisting of miR‐425 and miR‐21 . Moreover, the tumor suppressor miR‐218 regulates COX‐2 through the antiapoptotic NF‐κB signaling pathway .…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%
“…122 Apart from serving roles downstream of the PI3K/Akt pathway, NF-κB used to be moreover capable to have an effect on the expression of PTEN and downstream Akt signaling, mediated through its transcriptional regulation of miRNAs, consisting of miR-425 and miR-21. 123,124 Moreover, the tumor suppressor miR-218 regulates COX-2 through the antiapoptotic NF-κB signaling pathway. 125 OncomiR-370 used to be shown to decrease TGFβ -RII expression and stimulate TGFβ-1-induced phosphorylation of Smad3.…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%